TEACHING GRAMMAR AND VOCABULARY IN IT CONTEXT - Ibragimova, Shahnoza Turgunovna (Innovative Development in Educational Activities, 2023)
This article explores the importance of teaching grammar and vocabulary in an Information Technology (IT) context. It discusses various methodologies for integrating IT-related examples and exercises into lessons, such as the use of authentic materials and technology-based activities. The article emphasizes the need for educators to tailor their teaching methods to meet the specific needs of learners in the IT industry. The results of a comprehensive literature review are analyzed, highlighting successful approaches and their effectiveness. Overall, the article concludes that teaching grammar and vocabulary in an IT context is crucial for effective communication and understanding in the IT industry.